Effect of water bath‐assisted water extraction on physical and chemical properties of soybean oil body emulsion. Issue 12 (20th November 2020) - Han, Haotian; Zhao, Luping; Liu, Xiaonan; Guo, Anmin; Li, Xiangyang
Abstract: Soybean oil body (SOB), rich in polyunsaturated fatty acids and biologically active substances, is used as a natural emulsifier in food processing. In addition, SOB is healthier than synthetic emulsifiers. However, the physical and chemical properties of the SOB emulsion directly affect its application in food processing. In order to study the effect of water bath extraction (WBAE) on SOBs, the effects of WBAE method on the composition of SOBs, the zeta potential, average particle size, oxidation stability, and viscosity characteristics of SOB emulsions were researched. It was found that both protein and moisture contents of SOB decreased with increasing WBAE temperature; however, lipid content increased. These results were attributed to the exogenous proteins gradually denatured and dissociated with extraction temperature from 60°C to 100°C. Increasing the extraction temperature, the average particle size of the SOB emulsions increased, the oxidative stability was improved, the Zeta potential and viscosity decreased, and the fluidity of emulsions was improved. The SOB extracted at 100°C has broad application prospects in food, and this research is meaningful for supplying fundamental information for selecting proper extraction temperature of SOBs. Abstract : In order to study the effect of water bath extraction (WBE) on soybean oil bodies, the effects of WBE methods on the composition of soybean oil bodies and the zeta potential, average particle size, oxidation stability, and viscosity characteristics of soybean oil body emulsions were studied. The results show that the soybean oil body obtained by WBE has broad application prospects in food.